2019
DOI: 10.1039/c9ra01533g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiple environmental factors on the quality and flavor of watermelon juice

Abstract: Environmental factors (heat, pH, oxygen, light) can induce significant quality changes in watermelon juice during processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These results can be explained by a low level of damage to the starch grains of wheat flour while the addition of the watermelon puree increased the viscosity of the mixture and gas retention and therefore the optimization of the baking time reported that heated watermelon juice at 90°C has a higher viscosity. In the same way, the watermelon puree could increase the viscosity of this mixture [26]. These results are materialized by the gas evolution curve of the mixture which shows that the dough of this mixture has a good processing quality in bread making.…”
Section: Fermentative Ability Of Wheat Flour and Watermelon Puree Citrullus Lanatus (Thunb) Mixture Usable In Bread Making: A Preliminarymentioning
confidence: 57%
“…These results can be explained by a low level of damage to the starch grains of wheat flour while the addition of the watermelon puree increased the viscosity of the mixture and gas retention and therefore the optimization of the baking time reported that heated watermelon juice at 90°C has a higher viscosity. In the same way, the watermelon puree could increase the viscosity of this mixture [26]. These results are materialized by the gas evolution curve of the mixture which shows that the dough of this mixture has a good processing quality in bread making.…”
Section: Fermentative Ability Of Wheat Flour and Watermelon Puree Citrullus Lanatus (Thunb) Mixture Usable In Bread Making: A Preliminarymentioning
confidence: 57%